Letter - Bevin, Ernest, 1881-1951
1934-11-02 TELEGRAPHIC ADDRESS "TRANSUNION.PARL.LONDON" TELEPHONE VICTORIA 7671/5 TRANSPORT & GENERAL WORKERS UNION REGISTERED OFFICES, Transport House, Smith Square, WESTMINSTER, LONDON, S.W.1. General Secretary: ERNEST BEVIN. Financial Secretary, STANLEY HIRST Private EB/IS 2nd November, 1934. Mr. J. Bolton, T.U.C. Dear Mr. Bolton, Attached is a further letter from Edo Fimmin, for your perusal and return. Yours sincerely, Ernest Bevin 292/946/9/52